1991
DOI: 10.1037/0033-3204.28.3.395
|View full text |Cite
|
Sign up to set email alerts
|

A performance model of the creation of meaning event.

Abstract: Creation of meaning events are intherapy change episodes that occur when a patient seeks to understand the meaning of an emotional experience. Theoretical and empirical models of the patterns of change involved in creation of meaning events are presented. Three phases of the event with subphases are identified and illustrated. The next steps of the task-analysis of creation of meaning events are suggested.Research in psychotherapy recently has been advanced by the application of an information processing model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 8 publications
(12 reference statements)
1
20
0
Order By: Relevance
“…Even though many practitioners did not report that theory or research had much influence on their clinical work, it appears that most of them are also practicing in a way that is reasonably consistent with the current theoretical conceptions and empirical knowledge. For example, many practitioners endorsed engaging in therapeutic activities that fit with Clarke's (1989Clarke's ( , 1991Clarke's ( , 1993Clarke's ( , 1996 model of meaning creation work that emphasizes the symbolization and exploration of cherished beliefs and difficult emotions. Namely, storytelling, expressing and processing painful emotions, examining one's spiritual or existential concerns, using rituals and expressive/creative therapy techniques were all mentioned with considerable regularity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though many practitioners did not report that theory or research had much influence on their clinical work, it appears that most of them are also practicing in a way that is reasonably consistent with the current theoretical conceptions and empirical knowledge. For example, many practitioners endorsed engaging in therapeutic activities that fit with Clarke's (1989Clarke's ( , 1991Clarke's ( , 1993Clarke's ( , 1996 model of meaning creation work that emphasizes the symbolization and exploration of cherished beliefs and difficult emotions. Namely, storytelling, expressing and processing painful emotions, examining one's spiritual or existential concerns, using rituals and expressive/creative therapy techniques were all mentioned with considerable regularity.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the association between making sense of loss and adjustment, there has been surprisingly little attention given to how EOL professionals may facilitate such a process in actual therapeutic contexts. According to task analyses of meaning-making following a problematic experience (Clarke, 1989(Clarke, , 1991(Clarke, , 1993(Clarke, , 1996, which could presumably include experiencing a terminal illness or losing a loved one to death, people often experience an emotional protest and feel confused, surprised, and unable to formulate a sense of understanding. In particular, the clinical indicator for meaning creation has three identifying features: 1) strong emotional arousal; 2) challenge to a cherished belief; and 3) a lack of understanding or insight into the strong feelings.…”
Section: Introductionmentioning
confidence: 99%
“…They include empathic exploration of problem‐relevant experience, from which markers for other tasks typically emerge; experiential focusing (see Gendlin, 1996, for a number of in‐session processing difficulties; e.g., the client feels overwhelmed, blank, stuck or distanced from experience); and facilitating retelling of traumatic or difficult experiences, very common in experiential trauma work (Elliott, Davis, & Slatick, 1998). Also included is systematic evocative unfolding for problematic reaction points (i.e., puzzling overreactions to a specific situation; Watson & Rennie, 1994), and meaning work for strongly emotional meaning crises brought on by life events that challenge a cherished belief (Clarke, 1991). For example, Rebecca engaged in all of these tasks, particularly in the first half of her therapy, beginning with empathic exploration and facilitating retelling.…”
Section: Therapeutic Methods and Techniquesmentioning
confidence: 99%
“…Numerous studies have shown that language is an important human capability, providing individuals with the ability to reflect on and communicate experience, which makes unique contributions to mental health (Clarke, 1991, 1996; Pennebaker, 1993; Pennebaker & Graybeal, 2001; Pennebaker & Seagal, 1999). This study showed that the relationship between GBEL and mental health (depression and alexithymia) is mediated by both clarity of the self‐concept and anxiety experienced by individuals.…”
Section: Discussionmentioning
confidence: 99%
“…It is now accepted that the self is constructed by interpersonal or social transactions (Bamberg, 2000; Neimeyer & Mahoney, 2002). Clarke (1991, 1996) showed, in this respect, that the ability to express experiences clearly in words in the helping process accompanies successful sessions because it improves the extent to which individuals understand and give meaning to their experiences. Some findings showed, in this regard, that the benefits of talking were highly dependent on the social sharing (Lepore, Pablo, Ragan, & Ramos, 2004).…”
Section: Discussionmentioning
confidence: 99%